KETAHANAN PANGAN RUMAH TANGGA PETANI PADI, PETANI JAGUNG DAN NONPETANI DI KOTA METRO PROVINSI LAMPUNG - Sari, Desva; Indriani, Yaktiworo; Hasanuddin, Tubagus (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The purposes of this research are to analyze the level of food security and the factors that affect the level of food security. The research is conducted by survey method in Metro City that is chosen purposively as the research location. Respondents consisted of 17 paddy farmer households, 5 maize farmer households and 22 non-farmer households which were selected by simple random sampling. The data of income of farmers is analyzed by summing the total income from farming (Paddy and corn), non-farm income and non-agricultural income, while non-farm household income is obtained from the sum of the main work and gifts from children / siblings. Then to analyze the level of food security it is calculated based on the cross classification between the share of food expenditure and energy adequacy. The result of this research showed that the average of household income of paddy farmers was IDR 2,984,183/month, the average of household income of corn farmers was IDR 2,682,250/month and the average of household income of non-farmers was IDR 3,003,571/month. Most of the paddy farmer households were classified as less food (52.94%), as food secures (41.18%) and the rest respondents classified as vulnerable food (5.88%. Maize farmer households were classified as less food (80.00%) and as food secure (20.00%). Non-farm households were classified as less food (31.82%), as food secure (50.00%) and the rest respondents were classified as vulnerable food (18.18%). The factors that affected the level of food security are the formal education of household head. Key words: farmer and non-farmer households, food security.